THE EFFECTIVENESS OF TEACHING FOREIGN LANGUAGES THROUGH ONLINE PLATFORMS - Imomova Jasmina Sherali kizi (TADQIQOTLAR, 2026)
This article examines the effectiveness of teaching foreign languages through online platforms in modern educational settings. The study analyzes the role of digital technologies in improving students’ language skills, including listening, speaking, reading, and writing. Special attention is given to interactive tools, multimedia resources, and virtual communication opportunities that enhance learner engagement and motivation. The article also discusses the advantages and challenges of online language instruction, such as accessibility, flexibility, technical limitations, and learner autonomy. The findings suggest that online platforms significantly contribute to the development of communicative competence when used appropriately and systematically. The study concludes that integrating online platforms into foreign language teaching can increase the overall quality and effectiveness of the learning process.